(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
Effect of firing temperature on some physico-mechanical properties of ten brick samples, those were composed by feldspars, quartz, alumina-rich spinel, primary mullite and hematite phases, was investigated in accordance with ASTM standards. The brick samples fired between 700° to 1100° C showed 11-23 % water adsorptivity (WA), 19-37 % apparent porosity (AP) and 1.50-1.65 g/cm3 bulk density (BD) indicate good physical properties. The maximum compressive strength (CS) of the fired-bricks at 950° to 1000° C was found to be between 15.6 and 17.1 MPa. At 700°-1000° C firing temperatures, the CS of these bricks is found to be increased exponentially with decreasing of both WA and AP, however it is found to be increased with increasing the BD. Consequently, it can be said that there is good correlation between mechanical and physical properties of the fired-brick samples up to the firing temperature of 1000° C. Bangladesh J. Sci. Ind. Res.55(1), 43-52, 2020